A PSYCHOLOGICAL STUDY ON THE NARRATOR “I” IN EDGAR ALLAN POE’S ANNABEL LEE - Nugrahanti, Hesti (LANTERN (Journal on English Language, Culture and Literature), 2014)
Abstract, The purpose of this thesis is to analyze Edgar Allan Poe’s Annabel Lee. The writer intends to describe the mental state which the narrator endures upon Annabel Lee’s death. The writer discusses figurative language, namely symbol and irony, to describe the mental state in the poem. The writer adopts Sigmund Freud’s theory of levels of mental life and id ego superego, and John lee’s theory of obesessive love to describe the mental state. The methods of her intrinsic and the extrinsic discussion are applied through book observation, library research, and the internet browsing. The result shows that in a love relationship there are two kinds of moments, happy and sad one. This final academic paper shows that the death of the beloved one greatly affects the narrator’s life; he loses his self control and becomes deppressed.